2010
DOI: 10.1038/ni.1977
|View full text |Cite
|
Sign up to set email alerts
|

The splicing regulator PTBP2 interacts with the cytidine deaminase AID and promotes binding of AID to switch-region DNA

Abstract: During immunoglobulin class switch recombination (CSR), activation induced cytidine deaminase (AID) induces DNA double strand breaks into transcribed, repetitive DNA elements called switch sequences. The mechanism that promotes the binding of AID specifically to switch regions remains to be elucidated. We have used a proteomic screen that employs in vivo biotinylation of AID and have identified the splicing regulator polypyrimidine tract binding protein-2 (PTBP2) as an AID interactor. Short hairpin RNA-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
85
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 36 publications
4
85
1
Order By: Relevance
“…These studies provided compelling reasons to investigate the role of RNA processing during CSR. Recently published studies have implicated components of the RNA splicing machinery complex (CTNNBL1 and PTBP2) as being required for efficient CSR, thereby providing further cause for determining the exact role of RNA splicing in AID activity (Conticello et al 2008;Nowak et al 2011). The role of these factors and RNA splicing in general during SHM has not been thoroughly determined due to the lack of existing RNA splicing-deficient mouse models that can be a source of proliferating GC B cells.…”
Section: Rna Processing Pathways That Regulate Csrmentioning
confidence: 99%
“…These studies provided compelling reasons to investigate the role of RNA processing during CSR. Recently published studies have implicated components of the RNA splicing machinery complex (CTNNBL1 and PTBP2) as being required for efficient CSR, thereby providing further cause for determining the exact role of RNA splicing in AID activity (Conticello et al 2008;Nowak et al 2011). The role of these factors and RNA splicing in general during SHM has not been thoroughly determined due to the lack of existing RNA splicing-deficient mouse models that can be a source of proliferating GC B cells.…”
Section: Rna Processing Pathways That Regulate Csrmentioning
confidence: 99%
“…While GLT is non-productive due to stop codons in all three reading frames of I-exons, CSR needs I-exon splicing onto C H exons 7 . This might be due to the contribution of the splicing regulator PTBP2 to AID recruitment 8 . Recent evidence also suggested that, during CSR, AID directly recruits MMR and BER factors 2 .…”
mentioning
confidence: 99%
“…A number of cofactors have been identified by a combination of genetic and proteomic approaches, which suggest that AID synchronizes with other broadly important cellular pathways including, but not limited to, RNA splicing and processing (9, 10), cellular trafficking (11)(12)(13)(14), and transcription/RNA polymerase stalling (8,(15)(16)(17); however, a concise picture of the players involved in the AID reaction and the sequence of events remains unclear. Here, we use our solubility-based screening technique to identify a unique interacting partner for AID, RING finger protein 126 (RNF126).…”
mentioning
confidence: 99%